Productivity and Distribution of Fish Aggregation Devices (FADs) in Outer Ambon Bay Waters, Indonesia - Delly Dominggas Paulina Matrutty; Jacobus Bunga Paillin; Stany Rachel Siahainenia; Welem Waileruny; K Rutumalessy (Fisheries and Marine Science Faculty - Jenderal Soedirman University, 2021)
Distribution of small pelagis fish in FADs, and produktivity of FADs in AmFADs are usually used by fishermen to concentrate fish for an efficient catching activity. However, the number, distance, and distribution in the waters need to be assessed in relation to the productivity of the FADs in order to maintain the sustainability. This study was aimed to map the distribution of FADs; to analyze the distribution of species, number and size of fish associated with FADs; and to calculate FAD productivity based on distribution in the Outer Ambon Bay waters. Data was obtained by observation and interview. Field observation, including: coordinates and number of FADs, species, number and size of fish. The distance and distribution of FADs, was mapped using software (Argis web), while the productivity of FADs was analyzed base on catch per unit effort (CPUE). The result, FAD in Outer Ambon Bay waters was found 25 unit and the average distance of FAD was obtained 0.47 nautical miles, and the placement of the device was irregular. The placement pattern of FADs were generally straight to coastline. Small pelagic fish was found 7 species and the 5 of the dominant species were obtained Decapterus sp, Selar crumenophthalmus, Rastreliger sp, Sardinella sp and Selaroides sp. The species were unevenly spread at each FAD with quite varied sizes. FAD productivity showed that the highest productivity was found in the middle group FAD at Ambon Bay waters.Keywords: Distance, size, small pelagis, productivitybon Bay